Parlamint-it: an 18-karat UD treebank of Italian parliamentary speeches. - Alzetta, Chiara; Montemagni, Simonetta; Sartor, Marta; Venturi, Giulia (Language Resources & Evaluation, 2025)
The paper presents ParlaMint-It, a new treebank of Italian parliamentary debates, linguistically annotated based on the Universal Dependencies (UD) framework. The resource comprises 20,460 tokens and represents a hybrid language variety that is underrepresented in the UD initiative. ParlaMint-It results from a manual revision process that relies on a semi-automatic methodology able to identify sentences that are most likely to contain inconsistencies and recurrent error patterns generated by the automatic annotation. Such a method made the revision process faster and more efficient than revising the entire treebank. In addition, it allowed the identification and correction of annotation errors resulting from linguistic constructions inconsistently represented in UD treebanks and from characteristics specific to parliamentary speeches. Hence, the treebank is deemed as an 18-karat resource, since, although not fully manually revised, it is a valuable resource for researchers working on Italian language processing tasks.